(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out to find the effect of supplementation of lukewarm water during winter season on physiological parameters and production of Sahiwal cows. The present study was carried out with twelve healthy, lactating Sahiwal cows maintained at DDD farm within the premises of LFC of DUVASU, Mathura. These experimental cows were quasi randomly divided into two groups consisting six animals in each. All the cows were kept in conventional (tail-to-tail) system of housing for whole day. Cows of one group i.e. control were offered drinking water stored in water trough located in a corner of the shed at ambient temperature, whereas, the cows of supplemented group were offered lukewarm water at 25°C which was prepared by mixing of partial amount of warm water in cold water. Cows of both the groups were offered weighed amount of ad lib water thrice a day (early morning, afternoon and late evening) in graduated buckets individually. They were also provided weighed amount of ad lib feed. The production profile of control and treatment group were studied during the course of experiment and compared to observe the impact of supplementation of lukewarm water during winter season. A significant difference for total solid % (p<0.01) and SNF % (p<0.01) in experimental cows among 0, 1st, 2nd, 3rd, 4th and 5th fortnights were observed. But no significant (p>0.05) difference was observed in milk fat%, fortnight total milk yield (FTMY), fortnight daily milk yield (FDMY), total milk yield (TMY) and daily milk yield (DMY).